Annotated Bibliography of Life Coaching and Health Research - Courtney Newnham-Kanas; Paul Gorczynski; Don Morrow; Jennifer D. Irwin (International Journal of Evidence Based Coaching and Mentoring, 2009)
While executive life coaching is quite prominent in the research forum as outlined in Grant’s workplace and executive life coaching annotated bibliography (2005), studies pertaining to life coaching-related health outcomes are fewer in number and they have not been well recognized. Furthermore, although health-related studies focusing on life coaching as one form of health-related treatment have been conducted for some time, neither a summary nor an appraisal of the methodological soundness of these studies have been conducted. Therefore, the two-fold purpose of this annotated bibliography is: 1) to present a summary of critically appraised life coaching studies related to health research; and 2) stemming from that summary, to outline possible avenues for future health-related coaching research.